Realizacija principov Bolonskogo processa v Sankt Peterburgskom gosudarstvennom universitete fiziceskoj kul'tury im. P. F. Lesgafta - Orechov, E. F.; Kostjucenko, V. F.; Stepanov, V. S.; Sennikova, M. Ju. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
As the main line of development of higher education in modern Europe serves "Bologna process", supposing formation to 2010 of uniform European space of higher education. Saint-Petersburg state P.F.Lesshaft's university of physical culture having wide experience of training of the professional staff on powerful research base, rich pedagogical traditions, should become the branch leader in modernization of the Russian system of the high vocational training, in formation of uniform European educational space.